2021
DOI: 10.1038/s41467-021-25207-0
|View full text |Cite
|
Sign up to set email alerts
|

A pre-registered short-term forecasting study of COVID-19 in Germany and Poland during the second wave

Abstract: Disease modelling has had considerable policy impact during the ongoing COVID-19 pandemic, and it is increasingly acknowledged that combining multiple models can improve the reliability of outputs. Here we report insights from ten weeks of collaborative short-term forecasting of COVID-19 in Germany and Poland (12 October–19 December 2020). The study period covers the onset of the second wave in both countries, with tightening non-pharmaceutical interventions (NPIs) and subsequently a decay (Poland) or plateau … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
72
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(77 citation statements)
references
References 42 publications
5
72
0
Order By: Relevance
“…We found that the mean-ensemble model made the most accurate (as measured by median rWIS) and most consistently accurate (as measured by rWIS IQR) forecasts across forecast horizons, forecast dates and Trusts, overcoming the variable performance of the individual models. This is consistent with other COVID-19 forecast evaluation studies [ 8 , 14 , 21 , 23 ] and other diseases [ 25 , 27 , 48 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We found that the mean-ensemble model made the most accurate (as measured by median rWIS) and most consistently accurate (as measured by rWIS IQR) forecasts across forecast horizons, forecast dates and Trusts, overcoming the variable performance of the individual models. This is consistent with other COVID-19 forecast evaluation studies [ 8 , 14 , 21 , 23 ] and other diseases [ 25 , 27 , 48 ].…”
Section: Discussionsupporting
confidence: 92%
“…However, the utility of cases as a predictor for admissions is limited by the quality of case forecasts: whilst perfect case forecasts can improve forecasts of admissions, real-time case forecasts are not perfect and can lead to worse forecasts of admissions than simple trend-based models. Unfortunately, making accurate forecasts of COVID-19 cases in a rapidly-evolving epidemic is challenging [ 23 , 47 ], especially in the face of changing local restrictions. The Rt-based case forecasting model used here assumes no change in future Rt, so cannot anticipate sudden changes in transmission, for example due to a change in policy such as lockdowns.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In response, several organized modeling efforts were started to give public health officials as up to date information as possible about the trajectory of COVID-19 in the US and in Europe [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the US COVID-19 forecast hub, there are COVID-19 hubs that collect computational forecasts for Europe and specifically for Germany and Poland [11,13,14]. The majority of models submitted to these hubs are computational: statistical or dynamical models trained on structured data.…”
Section: Introductionmentioning
confidence: 99%